Paddy straw of precast wall - Zahari, Nur Anis Nadhirah; Abd Rashid, Mohd Najib; Mahyuddin, Muhammad Naim (2024)
The innovation project report titled Paddy Straw of Precast Panel explores the potential of utilizing paddy straw, a by-product of rice cultivation, as an eco-friendly alternative in the construction industry, specifically in the production of precast wall panels. With rice cultivation generating approximately 800 million tons of straw globally, the improper disposal of this biomass, often through open burning, poses significant environmental challenges, including greenhouse gas emissions and air pollution. This study aims to address the pressing issue of paddy straw waste management by investigating its incorporation into construction materials, thereby promoting sustainable practices. The research evaluates the mechanical properties of paddy straw cement composites, highlighting their strength, and acoustic properties. The project also emphasizes the importance of sustainable development in construction, aligning with global goals to reduce waste and enhance resource efficiency. Through comprehensive testing and analysis, the study seeks to demonstrate that paddy straw precast panels can not only reduce environmental impact but also enhance the performance of construction materials, thereby contributing to a more sustainable and economically viable construction sector. The findings aim to facilitate greater awareness and adoption of innovative building materials, ultimately supporting Malaysia's sustainability efforts in agriculture and environmental conservation.